Tinjauan Hukum terhadap Kewajiban Pembayaran Kredit Akibat Force Majeur pada Pembiayaan Konsumen - Dinda Putri Puspita; Erlina; Ade Darmawan Basri (Alauddin Law Development Journal)
The emergence of the Covid-19 outbreak has made the economy unstable, which is characterized by various policies such as PSBB, Lockdown,etc.making all activities hampered. The inhibition of all economic activities makes some people unable to meet the obligations that must be met, one of which is the obligation to make credit payments to Non-Bank institutions such as finance companies. Not fulfilling this obligation can certainly make the debtor a wansprestasi. But not fulfilling an obligation is certainly caused by various things, one of which is force majeure or commonly called Force Majeure. Force Majeure can be classified into two, namely absolud and realtif. Force Majeure caused by Covid-19 can be categorized in relative, where debtors can postpone their obligations for a while. Therefore, the government through the Financial Services Authority issued a policy related to POJK credit Restrutturization number 14 / POJK.05/2020 on Countercyclical policy impact of the spread of Coronavirus Disease 2019 for Non-Bank Financial Services Institutions